Metal additive manufacturing - Toyserkani, Ehsan; Sarker, Dyuti, 1983-; Ibhadode, Osezua Obehi, 1989-; Liravi, Farzad, 1990-; Russo, Paola, 1986-; Taherkhani, Katayoon, 1989- (Hoboken, NJ : Wiley, 2021)
"There are seven internationally recognized additive manufacturing (AM) technologies: i) vat polymerization processes, ii) material jetting, iii) material extrusion, iv) powder-bed fusion, v) sheet lamination, vi) directed energy deposition, and vii) powder-bed binder jetting. Laser metal AM processes fall in classes iv) and vi). In all seven classes, 3D objects are built by adding materials layer-by-layer, and AM has the potential to replace many conventional manufacturing processes as well as enable the development of new industry practices. This book covers additive manufacturing of metallic structures, with particular focus on laser-based and non-laser based AM processes. It also addresses the fundamentals, governing physics and modelling, as well as practical topics associated with these processes. The AM process starts with a CAD model as the basis for prototyping a replica and building the complete components through the injection of binder on pre-placed materials in selected regions or laser sintering of the pre-placed materials in the building bed. Whilst still a young technology, it has the potential to replace many conventional manufacturing processes as well as enable the development of new industry practices. Written by a leading expert in the field, the level is mixed to cover introductory, intermediate and advanced contents; the author has used the material in his own graduate course on laser additive manufacturing"--
BIBINDX
Keywords: Additive manufacturing; Metal powder products -- Design and construction; Powder metallurgy; Electronic books